Service Quality in E-Banking: An Empirical Study of Users' Perception - Sharma, Nishi (Indian Journal of Finance, 2012)
E-banking has revolutionized the entire traditional banking industry. Its countless benefits have made it an indispensable part of the financial system and it is one of the strongest catalysts for economic development. In developed nations, its burgeoning development is very much obvious, but in developing countries, the scenario is not that rosy. One important reason for low aptness of e-banking may be attributed to differences in the socio-psychological factors in these nations. Therefore, it is imperative to study the factors that are considered by the users of banking services before selecting any distribution channel. In this context, the present paper attempts to analyze the customers' perspective towards those qualitative aspects that e-banking must possess as its e-bankqual. The study is based upon primary data collected from 225 users of e-banking services. The internal consistency of data has been evaluated by Cronbach's Alpha test and sample adequacy has been tested by Kaiser-Meyer-Olkin Measure of sampling adequacy as well as Bartlett's Test of Sphericity. The questionnaire comprised of 26 questions, out of which 19 were related to the qualitative aspect of e-banking. As the degree of correlation detected the problem of multicollinearity, therefore, factor analysis was conducted. The analysis resulted in six variables, which are vital for securing the adhesion of customers to e-banking. These factors are Easiness In Transactions, Customer Relations, Efficient Processing, Secure Transactions, Availability of Services and Reporting (maintenance of records). The study is expected to provide significant insights to enhance the number of e-banking users, particularly in the context of developing nations.